What’s Next? A New Era (Comparative & International Education Series, 2021)
What’s Next? A New Era  Ryan M. Allen, Krishna Bista, and Roy Y. Chan The global pandemic has challenged everything we thought we knew about international higher education. National borders closed, college campuses were empty, and classrooms were completely digitized. What does a sector that thrived on global movement look like when no one can move? Is this the end of global higher education? The experiences and research presented throughout this volume have illustrated that the sector and its stakeholders will not let go that easy. As a community, we have survived and some have even thrived in these challenging times. This year experience under COVID-19 has changed the way that the world operates like no other event since World War II. In many ways, the post-World War II era defined and made possible the Golden Age of International Higher Education, especially after the Cold War, with robusts systems of education across the world and scholars, students moving to new places. Just as what happened after the war shaped the next fifty years, what happens after COVID will remake the world for the next fifty.